The Terrible Tetrad of Elbow is Not So Terrible if Individual Injuries are Managed Adequately: A Case Report - Kumar Keshav; Amarendra Singh; Siddhartha Singh; Sanjay Sharma (Journal of Orthopaedic Case Reports)
Introduction: The terrible triad of the elbow (TTE) is a well-described entity characterized by a triad of elbow dislocation, fractures of the radial head, and coronoid. Historically, these fractures gave poor clinical outcomes, and hence, the name “terrible triad.” There are many variants of TTE that may lead to poor prognosis if not adequately dealt with. One such variant is the association of TTE with olecranon fracture, which has not been adequately described in the literature. There have been just three papers (one case series and two case reports) on this variant of TTE, and the prognosis has been poor. We are describing one such case of “terrible tetrad of elbow.” Case Report: A 44-years-old male patient presented at 3 weeks following a road traffic injury with a painful, swollen left elbow and gross instability. Radiography revealed a terrible triad injury of the left elbow along with an olecranon fracture. The radial head was unsalvageable and required replacement by Kocher’s approach. Flexor carpi ulnaris (FCU) split medial approach was used for coronoid fixation. The same skin incision was used to reach the olecranon through FCU-extensor carpi ulnaris (ECU) interval. The olecranon was fixed with a 3.5 mm pre-contoured plate and coronoid by 2 lag screws passed in a posteroanterior direction and a 2.7 mm buttress T-plate. Intraoperatively, after bony fixations, there was no varus-valgus instability, and hence ligaments did not require repair. Post-operatively, the elbow was kept immobilized for 3 weeks, following which physiotherapy was started. At the final follow-up at 18 months, the patient achieved an excellent functional outcome based on the Mayo Elbow Performance Index. Conclusion: The Terrible tetrad of the Elbow seems challenging to manage with a historically dismal prognosis. It is critical to pay close attention to each destabilizing feature of the injury, which places a great demand on the surgeon’s understanding of the anatomic intricacies of the elbow. Management of these complicated constellations of injuries requires anatomic fracture fixation of the olecranon and coronoid, radial head fixation or replacement, and ligamentous repair or reconstruction, if any.